2022
DOI: 10.21873/anticanres.16008
|View full text |Cite
|
Sign up to set email alerts
|

An Appraisal to Address Health Consequences of Vitamin D Deficiency With Food Fortification and Supplements: Time to Act!

Abstract: A symposium entitled "Vitamin D in Prevention andTherapy" was held on May 4-5, 2022, in Homburg, Germany to discuss important new advances in the field, including identification of new vitamin D signaling pathways, of new biologic effects of vitamin D-compounds (e.g., on the microbiome), and convincing proof of the relevance of vitamin D deficiency for the risk and outcome of many chronic diseases, including cancer, cardio-vascular, auto-immune, metabolic, and infectious diseases. Concerning the COVID-19-pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…However, PSA is not cancer-specific, so it may be elevated in other non-malignant conditions [ 7 ]. Some studies have reported the importance of a good vitamin D status to prevent development and progression of prostate cancer [ 3 ], so we decided to carry out the present work to study this relationship in men without prostatic pathologies or liver or kidney failure. The hypothesis of this work is that vitamin D deficiency may lead to an increase in PSA for two reasons: 1) because low vitamin D concentrations induce prostate cancer and, therefore, in the population with low vitamin D concentrations there are more individuals with undetected prostate cancer than when vitamin D is high and 2) because low vitamin D concentrations increase PSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PSA is not cancer-specific, so it may be elevated in other non-malignant conditions [ 7 ]. Some studies have reported the importance of a good vitamin D status to prevent development and progression of prostate cancer [ 3 ], so we decided to carry out the present work to study this relationship in men without prostatic pathologies or liver or kidney failure. The hypothesis of this work is that vitamin D deficiency may lead to an increase in PSA for two reasons: 1) because low vitamin D concentrations induce prostate cancer and, therefore, in the population with low vitamin D concentrations there are more individuals with undetected prostate cancer than when vitamin D is high and 2) because low vitamin D concentrations increase PSA.…”
Section: Discussionmentioning
confidence: 99%
“…The active hormone binds to the vitamin D receptor (VDR) to regulate calcium and phosphorus metabolism, which is essential for bone remodeling, reabsorption of calcium in the distal tubule and intestinal absorption of calcium and phosphorus [ 1 , 2 ]. Although 1,25(OH) 2 D is the active hormone, serum concentration of 25(OH)D represents the best laboratory parameter to evaluate the vitamin D status [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, el PSA no es un marcador específico del cáncer, por lo que puede hallarse elevado en otras patologías no malignas [ 7 ]. A la luz de que algunos estudios muestran la importancia de un buen estado de vitamina D para prevenir el desarrollo y progresión del cáncer de próstata [ 3 ], realizamos este estudio para analizar su relación en hombres sin patologías prostáticas ni insuficiencia hepática o renal. Partimos de la hipótesis de que la deficiencia de vitamina D podría provocar un aumento del PSA por dos razones: (1) porque las concentraciones bajas de vitamina D inducen el cáncer de próstata y, por lo tanto, en la población con concentraciones bajas de vitamina D, se encuentra un mayor número de individuos con cáncer de próstata no detectado, a diferencia de cuando la vitamina D es elevada; y (2) porque las concentraciones bajas de vitamina D aumentan los niveles de PSA.…”
Section: Discussionunclassified
“…La hormona activa se une al receptor de la vitamina D (VDR) para regular el metabolismo del calcio y del fósforo, lo que es esencial para la remodelación ósea, la reabsorción del calcio en el túbulo distal y la absorción intestinal del calcio y el fósforo [ 1 , 2 ]. Aunque 1,25(OH) 2 D es la hormona activa, la concentración sérica de 25(OH)D es el parámetro analítico que se utiliza habitualmente para evaluar el estado de vitamina D [ 3 ].…”
Section: Introductionunclassified
“…Food fortification, oral supplementation with vitamin D and/or moderate UV-exposure to stimulate vitamin D production in skin are rated as safe to improve the vitamin D status of the population. Considering the high prevalence of vitamin D deficiency worldwide and the resulting severe consequences for human health, experts recommend that vitamin D deficiency urgently needs to be addressed in many countries by governments and healthcare authorities (5,6,(15)(16)(17) .…”
mentioning
confidence: 99%